Lynx behaviour around reindeer carcasses - Falk, Håkan (SLU/Dept. of Ecology, 2009)
The main prey for lynx in northern Sweden is semi-domestic reindeer. Lynx often utilise their large prey for several days and therefore a special behaviour can be observed around a kill site. The aim of this study was to investigate behavioural characteristics of lynx around killed reindeer and examine factors that might affect the behaviour. Data was collected in 2008 during two 6-weeks periods (winter and summer) from 4 lynx equipped with GPS-collars. In total 77 kill sites were analysed. Lynx spent on average 40 hours (SD=40) around a kill site but only about 10 hours (SD=11) within 50 meters of the carcass. Lynx revisited the carcasses on average 4 times (SD=3.5) and rested on average 898 meters (SD=1311) away from the carcass. I found that higher complexity in the environment such as steep slope and dense vegetation increased time spent around kill sites and shortened distance to resting sites, presumably because this is where lynx can feel safe. My results can be helpful in future predation studies, where it can aid interpretation of GPS-data and distinguish kill sites of reindeer from other clustered positions.